Antitumor efficacy of C‐X‐C motif chemokine ligand 14 in hepatocellular carcinoma in vitro and in vivo. Issue 11 (14th October 2013) - Wang, Weilin; Huang, Pengfei; Zhang, Lufei; Wei, Jianfeng; Xie, Qingsong; Sun, Qiang; Zhou, Xiaohu; Xie, Haiyang; Zhou, Lin; Zheng, Shusen
Abstract : C‐X‐C motif chemokine ligand 14 (CXCL14) is a novel gene that is expressed in many normal cells but is absent from or expressed at very low levels in cancerous tissues such as head and neck squamous cell carcinoma (HNSCC), prostate cancer, and pancreatic cancer. However, the relationship between CXCL14 and hepatocellular carcinoma (HCC) remains unclear. Therefore, the exact function of CXCL14, which may modulate antitumor immune responses in certain cancers, was evaluated. CXCL14 was downregulated in HCC tissues compared to adjacent normal tissues. Moreover, overexpression of CXCL14 had an inhibitory effect on cell proliferation, induced apoptosis and inhibited the invasion of HCC cells in vitro . Upregulation of CXCL14 by lentivirus also significantly suppressed the growth of subcutaneous tumors in nude mice in vivo . We further demonstrated that the loss of CXCL14 expression was regulated by promoter hypermethylation. CXCL14 induced tumor cell apoptosis through both the mitochondrial and nuclear apoptosis pathways. CXCL14 suppressed tumor cell proliferation through regulation of the cell cycle by downregulation of cyclins and cyclin‐dependent kinases. In conclusion, CXCL14 plays a pivotal role as a potential tumor suppressor in HCC. The re‐expression or upregulation of this gene may provide a novel strategy in HCC therapy in the future.